Rechallenge of denosumab in advanced giant cell tumor of the bone after atypical femur fracture: A case report and review of literature - Nasca, Vincenzo; Frezza, Anna Maria; Morosi, Carlo; Buonomenna, Ciriaco; Parafioriti, Antonina; Zappalà, Giorgio; Bini, Federica; Casali, Paolo Giovanni; Loppini, Mattia; Stacchiotti, Silvia (Frontiers in Oncology, 2022)
Giant cell tumor of bone (GCTB) is a rarely metastasizing neoplasm where surgery is often curative. Currently, the only available active therapeutic option for unresectable GCTB is denosumab, an anti-RANKL monoclonal antibody that dampens the aggressive osteolysis typically seen in this disease. For advanced/metastatic GCTB, denosumab should be continued life-long, and, although it is usually well tolerated, important questions may arise about long-term safety of this drug. In fact, uncommon but severe toxicities can occur and eventually lead to denosumab discontinuation, such as atypical fracture of the femur (AFF). The optimal management of treatment-related AFF is a matter of debate, and, to date, it is unknown whether reintroduction of denosumab at disease progression is a clinically feasible option, as no reports have been provided so far. Hereinafter, we present a case of a patient with metastatic GCTB who suffered from AFF after several years of denosumab; we describe the clinical features, orthopedic treatment, and oncological outcomes, finally providing the first evidence that denosumab rechallenge after AFF occurrence may be a safe and viable option at GCTB progression.